The Nuclear Mitotic Apparatus (NuMA) Protein: A Key Player for Nuclear Formation, Spindle Assembly, and Spindle Positioning - Kiyomitsu, Tomomi; Boerner, Susan (Frontiers in Cell and Developmental Biology, 2021)
The nuclear mitotic apparatus (NuMA) protein is well conserved in vertebrates, and dynamically changes its subcellular localization from the interphase nucleus to the mitotic/meiotic spindle poles and the mitotic cell cortex. At these locations, NuMA acts as a key structural hub in nuclear formation, spindle assembly, and mitotic spindle positioning, respectively. To achieve its variable functions, NuMA interacts with multiple factors, including DNA, microtubules, the plasma membrane, importins, and cytoplasmic dynein. The binding of NuMA to dynein via its N-terminal domain drives spindle pole focusing and spindle positioning, while multiple interactions through its C-terminal region define its subcellular localizations and functions. In addition, NuMA can self-assemble into high-ordered structures which likely contribute to spindle positioning and nuclear formation. In this review, we summarize recent advances in NuMA’s domains, functions and regulations, with a focus on human NuMA, to understand how and why vertebrate NuMA participates in these functions in comparison with invertebrate NuMA-related proteins.